Purification of soul in R.K. Narayan's, The Guide - Mani, Manimangai (Scottish Group, 2013)
R.K. Narayan is one of the most well known novelist in India who writes in English. He is well known for his depiction and humourous writing on Indian society and culture. R.K. Narayan is essentially a storyteller, whose sensitive, well-drawn portrayals of twentieth-century Indian life were set mostly in the fictional South Indian town of Malgudi. Most of his novels capture many Indian traits while having a unique identity of their own. The Guide, which is also set in the town of Malgudi is written in a simple style, unpretentious, and witty with a unique flavour as if he was writing in the native mother tongue. The story seems to depict the everyday life of the simple characters in a rather amusing and comical way. But at the same time one can‘t help to wonder if R.K Narayan, who is hailed as a master story teller of India, has only the motive of entertaining and being comical in this book. I belief R.K Narayan has a wider and rather philosophical message beneath his work. From pages to pages of this novel, I noticed how the author holds dear to the age old philosophy that underlines the core of Hinduism –the law of Karma. Therefore, to understand The Guide,one needs to understand the theological aspects of Hinduism. This novel actually takes the readers on a journey of Hinduism and shows how the transition and purification of a Hindu soul takes place through the main character, Raju. Narayan shows how Raju, a character full of flaws goes through different phases in his life to redeem his sins and become a changed person towards the end.